Lactobacillus spp. for Gastrointestinal Health: Current and Future Perspectives - Dempsey, Elaine; Corr, Sinéad C. (Frontiers in Immunology, 2022)
In recent decades, probiotic bacteria have become increasingly popular as a result of mounting scientific evidence to indicate their beneficial role in modulating human health. Although there is strong evidence associating various Lactobacillus probiotics to various health benefits, further research is needed, in particular to determine the various mechanisms by which probiotics may exert these effects and indeed to gauge inter-individual value one can expect from consuming these products. One must take into consideration the differences in individual and combination strains, and conditions which create difficulty in making direct comparisons. The aim of this paper is to review the current understanding of the means by which Lactobacillus species stand to benefit our gastrointestinal health.